2019
DOI: 10.52429/selju.v2i1.228
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Communication Strategies of Youtube Video by Students of English Department in Unimus

Abstract: This research aims at explaining communication strategies (CS) used by the 4 th semester students of English education in University of Muhammadiyah Semarang. Data gained from the transcription of YouTube video in each channel owned by students. This descriptive qualitative study observed the frequency of communication strategies employed by students by analyzing their utterance used Tarone's typologies of communication strategies. Based on the analysis, it can be seen that the use of communication strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Dari hasil pengabdian di atas dapat disimpulkan bahwa kemampuan berbicara para terapis meningkat dan termotivasi berbicara bahasa Inggris kepada pelanggan klinik Seger Waras ketika menemui pelanggan dari luar negeri. Hasil ini sejalan dengan kegiatan pengabdian dan penelitian dari para ahli sebelumnya (Budiastuti & Wijayatiningsih, 2019;Susilowati et al, 2017;Wijayatiningsih et al, 2015).…”
Section: Gambar 4 Pelaksanaan Pelatihanunclassified
“…Dari hasil pengabdian di atas dapat disimpulkan bahwa kemampuan berbicara para terapis meningkat dan termotivasi berbicara bahasa Inggris kepada pelanggan klinik Seger Waras ketika menemui pelanggan dari luar negeri. Hasil ini sejalan dengan kegiatan pengabdian dan penelitian dari para ahli sebelumnya (Budiastuti & Wijayatiningsih, 2019;Susilowati et al, 2017;Wijayatiningsih et al, 2015).…”
Section: Gambar 4 Pelaksanaan Pelatihanunclassified
“…Riana and Testiana focuses their research into speaking skill and they finds the problems of speaking is about difficulties to express their feeling. A research of Riana and Testiana using technology for solving the problem by video in youtube and showed that this method can increase their speaking skill (Budiastuti and Wijayatiningsih, 2019).…”
Section: Introductionmentioning
confidence: 99%